2022
DOI: 10.3390/ijms23169000
|View full text |Cite
|
Sign up to set email alerts
|

The IRE1α–XBP1s Arm of the Unfolded Protein Response Activates N-Glycosylation to Remodel the Subepithelial Basement Membrane in Paramyxovirus Infection

Abstract: Respiratory syncytial virus (RSV) causes severe lower respiratory tract infections (LRTI) associated with decreased pulmonary function, asthma, and allergy. Recently, we demonstrated that RSV induces the hexosamine biosynthetic pathway via the unfolded protein response (UPR), which is a pathway controlling protein glycosylation and secretion of the extracellular matrix (ECM). Because the presence of matrix metalloproteinases and matricellular growth factors (TGF) is associated with severe LRTI, we studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Although EMP is orchestrated by interactions of the IKK signaling with multiple intracellular phosphorylation cascades, maintenance of the EMT pathway is dependent on cellular survival and adaptation to ER stress through protein N-glycosylation ( 13 , 37 ). EMP-induced N-glycosylation is dependent on the abundance of intracellular uridine 5′-diphosphate-N-acetyl-d-glucosamine (UDP-GlcNAc), which is a rate-limiting substrate for N-glycan synthesis and subsequently N-glycosylation of asparagines on secreted proteins, enabling proper protein folding, transport to Golgi and secretion, relieving proteotoxicity ( 13 , 37 ). The details of how IRE1α-XBP1s pathway controls UPR-induced metabolic adaptations are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although EMP is orchestrated by interactions of the IKK signaling with multiple intracellular phosphorylation cascades, maintenance of the EMT pathway is dependent on cellular survival and adaptation to ER stress through protein N-glycosylation ( 13 , 37 ). EMP-induced N-glycosylation is dependent on the abundance of intracellular uridine 5′-diphosphate-N-acetyl-d-glucosamine (UDP-GlcNAc), which is a rate-limiting substrate for N-glycan synthesis and subsequently N-glycosylation of asparagines on secreted proteins, enabling proper protein folding, transport to Golgi and secretion, relieving proteotoxicity ( 13 , 37 ). The details of how IRE1α-XBP1s pathway controls UPR-induced metabolic adaptations are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the UPR involves expression of immediate-early homeostatic genes that prevent proteotoxicity via protein N-glycosylation ( 13 , 37 ). Our previous ATAC-Seq studies have shown that the majority of RSV-inducible genes are silent, yet maintained in an open chromatin configuration associated with H3K27Ac marks ( 16 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, enrichment of extracellular matrix-related genes was specific to RSV infection compared with both the non-RSV infection and control groups. Studies have indicated that RSV infection could potentiate changes in extracellular matrix dynamics, which might be linked to asthma development ( 22 24 ). RSV-infected human lung fibroblasts could induce hyaluronan-enriched extracellular matrix production, promoting the adhesion of mast cells, which have long been recognized as a type of critical cell in the development of allergic airway inflammation and asthma.…”
Section: Discussionmentioning
confidence: 99%